Outcomes After Declining a Steatotic Donor Liver for Liver Transplant Candidates in the United States. Issue 8 (August 2020) - Jackson, Kyle R.; Bowring, Mary G.; Holscher, Courtenay; Haugen, Christine E.; Long, Jane J.; Liyanage, Luckmini; Massie, Allan B.; Ottmann, Shane; Philosophe, Benjamin; Cameron, Andrew M.; Segev, Dorry L.; Garonzik-Wang, Jacqueline
Abstract : Background: Steatotic donor livers (SDLs, ≥30% macrosteatosis on biopsy) are often declined, as they are associated with a higher risk of graft loss, even though candidates may wait an indefinite time for a subsequent organ offer. We sought to quantify outcomes for transplant candidates who declined or accepted an SDL offer. Methods: We used Scientific Registry of Transplant Recipients offer data from 2009 to 2015 to compare outcomes of 759 candidates who accepted an SDL to 13 362 matched controls who declined and followed candidates from the date of decision (decline or accept) until death or end of study period. We used a competing risk framework to understand the natural history of candidates who declined and Cox regression to compare postdecision survival after declining versus accepting (ie, what could have happened if candidates who declined had instead accepted). Results: Among those who declined an SDL, only 53.1% of candidates were subsequently transplanted, 23.8% died, and 19.4% were removed from the waitlist. Candidates who accepted had a brief perioperative risk period within the first month posttransplant (adjusted hazard ratio [aHR]: 2.49 3.494.89, P < 0.001), but a 62% lower mortality risk (aHR: 0.31 0.380.46, P < 0.001) beyond this. Although the long-term survival benefit of acceptance did not vary by candidate model for end-stage liver disease (MELD), the short-term risk period did. MELD 6–21 candidates who accepted an SDL had a 7.88-fold higher mortality risk (aHR: 4.80 7.8812.93, P < 0.001) in the first month posttransplant, whereas MELD 35–40 candidates had a 68% lower mortality risk (aHR: 0.11 0.320.90, P = 0.03). Conclusions: Appropriately selected SDLs can decrease wait time and provide substantial long-term survival benefit for liver transplant candidates.